2020
DOI: 10.1111/dom.13968
|View full text |Cite
|
Sign up to set email alerts
|

ADVANCE in context: The benefits, risks and feasibility of providing intensive glycaemic control based on gliclazide modified release

Abstract: In the last 3 decades, four large multicentre, randomized clinical trials of patients with type 2 diabetes (UKPDS, ADVANCE, ACCORD and VADT) have studied different approaches to achieving near normal glycaemic targets. Each was designed against a background of international and national guidelines recommending glycaemic targets of 6.5% or less to prevent diabetic complications. Collectively, these clinical trials provide the most robust evidence of the potential vascular benefits and risks of more versus less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Despite inconsistent findings, 28 metformin could be associated with reduced risk of cardiovascular-related events and cardiovascular mortality in patients with T2D, 29,30 and this benefit may offset or modify the risk of the cardiovascular events associated with found that the mitoK ATP channel low-affinity sulfonylurea gliclazide modified release vs other antidiabetic medication and linagliptin vs the mitoK ATP channel low-affinity sulfonylureas glimepiride, respectively, had comparable outcomes on the risk of MACEs. 31,32 Although not directly comparable to this current study, the data from the 2 large prospective studies 31,32 indirectly support our reported data.…”
Section: Discussionsupporting
confidence: 50%
“…Despite inconsistent findings, 28 metformin could be associated with reduced risk of cardiovascular-related events and cardiovascular mortality in patients with T2D, 29,30 and this benefit may offset or modify the risk of the cardiovascular events associated with found that the mitoK ATP channel low-affinity sulfonylurea gliclazide modified release vs other antidiabetic medication and linagliptin vs the mitoK ATP channel low-affinity sulfonylureas glimepiride, respectively, had comparable outcomes on the risk of MACEs. 31,32 Although not directly comparable to this current study, the data from the 2 large prospective studies 31,32 indirectly support our reported data.…”
Section: Discussionsupporting
confidence: 50%
“…According to the 2020 ADA guidelines of DM ( 18 ) and 2017 A Position Statement of DR ( 13 ), the participants were assigned to the DM group {no DR, 32 patients, aged 37–75 years, median [interquartile range (IQR)]: 56 (48–65) years}, non-proliferative diabetic retinopathy group [NPDR group) [56 patients, aged 29–76 years, 56 (51–61)] years], and PDR group [43 patients, aged 27–74 years, 55 (49–60) years].…”
Section: Methodsmentioning
confidence: 99%
“…Numerous international large-scale epidemiological studies, including the UK Prospective Diabetes Study (UKPDS, follow up for 10 years) ( 9 ), The Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified Release Controlled Evaluation (ADVANCE, follow up for 4.3 years) ( 10 ), the Action to Control Cardiovascular Risk in Diabetes (ACCORD, follow up for 4 years) ( 11 ), and the Veteran Affairs Diabetes Trial (VADT, follow up for 5 years) ( 12 ) have demonstrated that even though the multiple risk factor interventions (hyperglycemia, blood pressure, and lipid regulation) can effectively reduce the risk of diabetic microvascular disease (DMVC), 51% of diabetic patients still develop DR (51% of those with DR) and DKD (25% of individuals with DKD) ( 13 ). DMVC (the residual risk of DMVC) that still exists after comprehensive management of diabetic patients is a major challenge for both ophthalmologists and endocrinologists.…”
Section: Introductionmentioning
confidence: 99%
“…The ADVANCE trial began to recruit nearly 20 years ago 1 and it is apposite to review the trial results in the light of the history and progress made in therapeutics in the treatment of type 2 diabetes since the main results were published in 2008. 2 In this series of articles in this supplement, Zoungas, Knudsen & Cooper, Chalmers & Woodward, and Marre outline the history and the findings on the ADVANCE trial in some detail, covering explicitly the lessons learned about glycaemic control, 3 renal disease, 4 observational studies, 5 and blood pressure (BP) control. 6 Long-term outcome trials are expensive and labour-intensive.…”
mentioning
confidence: 99%
“…In this series of articles in this supplement, Zoungas, Knudsen & Cooper, Chalmers & Woodward, and Marre outline the history and the findings on the ADVANCE trial in some detail, covering explicitly the lessons learned about glycaemic control, renal disease, observational studies, and blood pressure (BP) control …”
mentioning
confidence: 99%